MODEL PENAWARAN DAN PERMINTAAN MINYAK KELAPA SAWIT INDONESIA DI PASAR INTERNASIONAL - Tia Sofiani Napitupulu; Djaimi B akce; Almasdi Syahza; Brilliant Asmit; Syaiful Hadi (DINAMIKA PERTANIAN, 2019)
ABSTRACT Indonesia is the leading producer of palm oil in the world. In 2016 Indonesia and Malaysia produced 81% of the world's palm oil. This study aims to analyze the response of the supply and demand for Indonesian palm oil in the world market. This study used time-series data from 1980-2016. The model built is an econometric model, simultaneous equations. To answer the research objectives, the data were analyzed using the Two Stages Least Square (2SLS) method. The main finding of this study is that in the short term, there are no responsive variables. In the long term, the variable that is responsive to the supply of Indonesian palm oil is the lag area of Indonesian palm oil. In the Malaysian palm oil supply equation, the response variable is the lag area of Malaysian palm oil. In terms of domestic demand for Indonesian palm oil, there are no responsive variables both in the short and long term. In the equation of demand for Malaysian palm oil, the responsive variables are the price of Malaysian palm oil and the price of Malaysian coconut oil. In the international demand for palm oil, the responsive variables are the increase in world palm oil prices, world palm oil prices, 2-year lag in world palm oil prices, and GDP per capita Pakistan. In terms of price, the responsive variable affecting the price of Indonesian palm oil is the world price of palm oil.